2014
DOI: 10.1152/ajpendo.00542.2013
|View full text |Cite
|
Sign up to set email alerts
|

miR-24 regulates menin in the endocrine pancreas

Abstract: Vijayaraghavan J, Maggi EC, Crabtree JS. miR-24 regulates menin in the endocrine pancreas. Am J Physiol Endocrinol Metab 307: E84 -E92, 2014. First published May 13, 2014; doi:10.1152/ajpendo.00542.2013.-Menin, the product of the MEN1 gene, functions as a tumor suppressor and was first identified in 1997 due to its causative role in the endocrine tumor disorder multiple endocrine neoplasia, type 1 (MEN1). More recently, menin has been identified as a key player in pancreatic islet biology with the observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 59 publications
1
38
0
1
Order By: Relevance
“…Moreover, patients with late stage PSC have increased MEN1 expression compared to controls with early disease [102]. MiR-24 can target a complementary site on MEN1, and it has been shown that increasing MEN1 correlates with increasing expression of fibrosis genes (e.g., fibronectin 1, collagen type 1 α 1, tumor growth factor β 1 and α-smooth muscle actin) [102,103]. Menin, the protein product of MEN1, which itself is a tumor suppressor gene, may thus be responsible for mediating the cholangiocyte response cholangiocytes to injury [102].…”
Section: The Role Of Mirna In Cholangiocyte Homeostasis and Pathologymentioning
confidence: 99%
“…Moreover, patients with late stage PSC have increased MEN1 expression compared to controls with early disease [102]. MiR-24 can target a complementary site on MEN1, and it has been shown that increasing MEN1 correlates with increasing expression of fibrosis genes (e.g., fibronectin 1, collagen type 1 α 1, tumor growth factor β 1 and α-smooth muscle actin) [102,103]. Menin, the protein product of MEN1, which itself is a tumor suppressor gene, may thus be responsible for mediating the cholangiocyte response cholangiocytes to injury [102].…”
Section: The Role Of Mirna In Cholangiocyte Homeostasis and Pathologymentioning
confidence: 99%
“…However, a consensus signature of genes affected upon menin loss in MEN1 target tissues warrants further investigation. Regarding the regulation of menin, a microRNA (miR24-1 and its mature form miR24) has been shown to regulate the expression of menin with a feedback mechanism (Luzi, et al 2012; Vijayaraghavan, et al 2014). Further studies of this miRNA that targets menin may shed light on yet another aspect of the multi-functional roles of menin and its regulation.…”
Section: The Men1 Encoded Protein Menin and Its Functional Characterimentioning
confidence: 99%
“…Menin has been shown to directly bind to JunD, an AP-1 transcription factor, to facilitate histone deacetylation and turn off transcription of JunD targets. It has also been shown to enable transcription of mixed-lineage leukemia (MLL) protein target genes by modifying histones with activating tri-methylation marks 9,10 .…”
Section: Menin Structure and Functionmentioning
confidence: 99%
“…One explanation for menin’s broad and variable role is the 5′ heterogeneity of the MEN1 mRNA transcript 10 . Northern blot, 5′ RACE, and positional deletion studies revealed that the MEN1 transcripts come in two sizes: a ubiquitously expressed 2.8-kb transcript and a larger 4.2-kb transcript with expression restricted to the pancreas and thymus 16 .…”
Section: Men1 Isoformsmentioning
confidence: 99%
See 1 more Smart Citation